Ability of Non-Medical Female Employees Towards Self Breast Assessment - Desai, Purnima M.; Gholap, Manisha C. Gholap; Shinde, Mahadeo B; Choudhari, Samir K. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The breast cancer is commonly found among women in developing countries. Early detection plays a very important role in breast cancer,the Breast self-examination is simple, non-invasive and inexpensive method. Objectives: (1) To assess the existing knowledge regarding self breast examination among non-medical female employees.(2) To assess the capacity to do self breast examination among non-medical female employees. (3) To find the association between existing knowledge score with selected socio demographic variables. Methods:Evaluative research approach, The participants consists of 49 non medical female employees were selected through purposivesampling technique. The data were collected by structured questionnaire. The data analyzed using spss software. Results: The pre-testmean knowledge score was 4.551 and post-test mean score was 17.265.The t-test value was 61.053 and was found significant at p<0.0001 level.The freqency and percentage of selected socio-demographic variable are, manjority of female employees age group from 30-39 years and 40- 49 years 22 (44.89%), majority of them are Hindu 32 (65.30%). Most of them are married 37 (75.51%). Majority are from rural residents 30 (61.27%). Most of them having 2 children 33 (67.34%). None of them has history of breast cancer in first relatives i.e. 0%. Majority of them had primary education 24 (48.97%).Conclusion:The health teaching program specially the demonstrations improves the capacity to do the breast self examination such program should be conducted more frequently.